Estructura y composición del bosque remanente del área de influencia del humedal Abras de Mantequilla ubicado en el cantón Vinces, provincia de Los Ríos - Reyes Bobadilla, Jessica Angélica (2021)
Abras de Mantequilla it is a natural and permanent system of swamps and lakes, influenced by the existence of small streams and seasonal winter lakes that flow into a large lake; it has an area of 22,500 km2. This research project was carried out with the objective of determining the structure and composition of the remaining forest in the area of influence of the Abras de Mantequilla wetland, belonging to the Vinces canton. An inventory of the eight parcels present in the forest remnant was carried out, of which the diameter and total height of the individuals, species, family were taken into account, with the use of the importance value index (IVI) and Importance value of families (IVF), the floristic composition and structure of the vegetation present was demonstrated. A total of 322 individuals belonging to 19 families and 41 species were recorded, the Fabaceae being the most diverse. The importance value index (IVI) indicated that the species Cochlospermum vitifolium Spreng., Guazuma ulmifolia, Schinopsis balansae., Are the most representative in the study area, with 28.21%, 24.93%, 22.11% respectively. The Shannon index is 2.81, thus indicating that it has a high diversity of species, and the Jaccard index shows that there is no similarity between the eight species plots. At the level of plots, the most abundant was that of 2 m x 2 m, with 117 individuals; however, the 20 m x 20 m one registered 115 species. The results obtained from the structures in the plots made indicate that the trees do not exceed 20 meters in height, in addition, most of the DBH is varied, this indicates that there is not much heterogeneity between the species. Keywords: Heterogeneity, forest remnant, diversity, index, plots, species, family, individuals